Ligand-controlled regiodivergent direct arylation of indoles via oxidative boron Heck reaction. Issue 21 (21st September 2022) - Yang, Yo-Sep; Lee, Sangmin; Son, Seung Hwan; Yoo, Hyung-Seok; Jang, Yoon Hu; Shin, Jeong-Won; Won, Hyuck-Jae; Sim, Jaehoon; Kim, Nam-Jung
Abstract : Ligand-controlled direct arylation of indoles via Pd(ii ) catalyzed oxidative boron Heck reaction under aerobic conditions is reported. Abstract : Ligand-controlled direct arylation of indoles via Pd(ii ) catalyzed oxidative boron Heck reaction under aerobic conditions is reported. This methodology provides a regiodivergent route for C2 or C3 aryl indoles in a protection free and acid/base free manner.